Development of simple random mutagenesis protocol for the protein expression system in Pichia pastoris. Issue 1 (December 2016) - Tachioka, Mikako; Sugimoto, Naohisa; Nakamura, Akihiko; Sunagawa, Naoki; Ishida, Takuya; Uchiyama, Taku; Igarashi, Kiyohiko; Samejima, Masahiro
Abstract Background Random mutagenesis is a powerful technique to obtain mutant proteins with different properties from the wild-type molecule. Error-prone PCR is often employed for random mutagenesis in bacterial protein expression systems, but has rarely been used in the methylotrophic yeastPichia pastoris system, despite its significant advantages, mainly because large (μg-level) amounts of plasmids are required for transformation. Results We developed a quick and easy technique for random mutagenesis inP. pastoris by sequential Phi29 DNA polymerase-based amplification methods, error-prone rolling circle amplification (RCA) and multiple displacement amplification (MDA). The methodology was validated by applying it for random mutation of the gene encoding cellulase from the basidiomycetePhanerochaete chrysosporium (Pc Cel6A), a key enzyme in degradation of cellulosic biomass. In the error-prone RCA step, the concentrations of manganese ion (Mn2+ ) and cellulase gene-containing plasmid were varied, and the products obtained under each condition were subjected to the second MDA step in the absence of Mn2+ . The maximum error rate was 2.6 mutations/kb, as evaluated from the results of large-scale sequencing. Several μg of MDA products was transformed by electroporation intoPichia cells, and the activities of extracellularly expressedPc Cel6A mutants towards crystalline and amorphous celluloses were compared with those of wild-type enzyme to identify key amino acid residues affecting degradation of crystalline cellulose. Conclusions We present a rapid and convenient random mutagenesis method that does not require laborious steps such as ligation, cloning, and synthesis of specific primers. This method was successfully applied to the protein expression system inP. pastoris .